60.6k views
0 votes
Solve the system using substitution. show work.
x=y−6
y=6−3x

1 Answer

1 vote

Answer:

y=6

x=0

Explanation:

X=(y-6)

y=(6-3x)

So For Y

y=6-3(y-6)

y=6-3y+18

add three so it would be 4y=6+18 which then equal 4y=24 then divide 4 then you'll have 6

and for X just plug in whats in (y)

x=(6-3x)-6

So again add 3x to both side to get 4x=6-6 which equal 0 then answer is 4x=0 divide 4 get 0

User Oghli
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.